PRODUCTIVE PERFORMANCE OF HOLSTEIN COWS IN A MIXED PASTURE OF PEARL MILLET AND COWPEA WITH AND WITHOUD SUPLEMENTATION - HANISCH, Ana Lúcia; ABREU DA SILVA, Marcelo; MEDEIROS, Renato Borges de (Scientia Agraria, 2010)
Holstein cows milk production were evaluated under two grazing management systems: a mixed pasture of pearl millet (Pennisetum glaucum (L.) R. Brown) and cowpea (Vigna unguiculata L.) with or without supplementation to the animals, during the period of 18/12/2000 a 20/02/2001. Twelve multipara cows of the Holstein breed were used. They were selected by their production potential, live weight (LW) and lactation period. After the stratification, the animals were randomly distributed between the two treatment groups of the experiment: animals kept under grazing in a mixed pasture of pearl millet and cowpea; and animals kept in the same pasture receiving supplementation in a daily basis. The experiment was carried out in a completely randomized design. The average dry matter was 2469 kg ha-1 at the entrance and 1554 kg ha-1 at the animal exit from the enclosed pasture. The harvest pasture dry matter presented 16.5 dag kg-1 of crude protein, 68.5 dag kg-1 of neutral detergent fiber and 70.25 dag kg-1 of digestibility in vitro of organic matter. The average participation of Cowpea in the mixture pasture was 12%. There was a significant difference in milk production of milk between the two grazing systems treatments. The average milk productions were 19.56 kg day-1 to cows receiving only pasture and 23.40 kg day-1 to the ones supplemented. The supplementation promoted more stability in cow milk production between the evaluation periods.